The Effect of Simultaneous Training On Some Bio-kinematical Variables and 2000m Youth Rowing Race Achievement - Ismael, Faten; Abedullatef, Ayad (Journal of Physical Education, 2017)
The importance of the research lies in connecting performance with training aidand training type in a training program designed scientifically. The problem of the researchlies in the lack of bio – kinematical variables measurement results found through analysisthat could help coaches as a training aid. The aim of the research was designing a trainingprogram and identifying the effect of this training program on some bio – kinematicalتأثير التدريب المتزامن في بعض المتغيرات البايوكينماتيكيةوانجاز سباق 2000م تجديف )Rowing )شبابأ.م.د. فاتن اسماعيل محمد م.م. اياد عبد اللطيف علي1438 هـ2017م191مجلة كلية التربية الرياضية – جامعة بغداد ✽ المجلد التاسع والعشرون ✽ العدد الثاني ✽ لسنة2017variables and 2000m rowing race achievement. The researchers hypothesized statisticaldifferences in some bio – kinematical variables between pre and posttests in bothexperimental and controlling groups. The researchers used the experimental method. Theyconcluded that the training program developed the physical aspects of rowing that wasreflected on the skill of performance. The researchers recommended giving more time forendurance training before starting simultaneous training